Environmental accounting concepts and their relation to the sustainability paradigm - Araujo Fernandes da Costa , Laís; Luzia Álvares dos Prazeres , Karla; Joviniano Álvares dos Prazeres , Paulo; Alex da Silva Torres , Rafael (Seven Editora, 2023)
This article aims to demonstrate the perception of accounting professionals in regarding the level of knowledge of environmental accounting and conceptualize it. Environmental issues are increasingly strong in everyday life, so companies and accountants use environmental accounting as their accounting management and control system, including environmental information in their statements. With the market growing and becoming more competitive, societies generally want organizations that are more environmentally responsible, so that companies keep the idea of environmental preservation. And this is where the role of the accountant comes in, helping the company to fulfill its social role, respecting the environmental legislation and the environment in which it lives. Nowadays it becomes a very important subject for companies, because, besides the rules of the legislation, they suffer pressure from environmental groups and associations. Companies are already thinking about the rationalization side of their natural resources and are still investing in new and better technologies that are cleaner and produce more environmentally friendly goods. Environmental accounting can be considered a great tool to assist decision-making processes by providing relevant information. The care taken by companies for the environment can be an important strategy for the development of the organization, seeking satisfaction of customers, employees and other people who use the company's service in relation to the level of products and services provided. DOI: https://doi.org/10.56238/tfisdwv1-022